A pseudo-rotaxane of α-cyclodextrin and a two-station axis molecule consisting of pyridinium and decamethylene moieties, and its deuteration in deuterium oxide. Issue 33 (17th August 2017) - Hashidzume, Akihito; Kuse, Akihiro; Oshikiri, Tomoya; Adachi, Seiji; Yamaguchi, Hiroyasu; Harada, Akira
Abstract: We prepared a two-station axis molecule possessing a 2-methylpyridinium moiety at an end, which regulates the direction of inclusion by α-cyclodextrin (α-CD). In the two-station axis molecule, the two decamethylene station moieties are linked through a pyridinium, over which α-CD can shuttle rather freely between the stations. We observed the formation of pseudo-rotaxane from the two-station axis molecule and α-CD at higher temperatures (≥50 °C). During the formation of pseudo-rotaxane in D2 O, we happened to find that the methyl and methylene groups on the 2- and 4-positions of pyridinium moieties underwent α-CD-catalyzed deuteration. The deuteration proceeded faster at a higher temperature. The apparent activation energy was estimated from the Arrhenius plot. Graphical abstract: